2018
DOI: 10.1002/mus.26069
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue is a relevant outcome in patients with myasthenia gravis

Abstract: Fatigue in myasthenia correlates with disease severity, affects QoL, and can improve after treatment. Muscle Nerve 58: 197-203, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
42
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 25 publications
5
42
1
2
Order By: Relevance
“…However, although males had more depression that was significantly correlated with disease severity, women were more likely to have greater disease severity. Previous studies have shown similar gender differences in MG severity and QoL with women having worse fatigue and QoL than men [31,32]. Our study is in keeping with those findings.…”
Section: Discussionsupporting
confidence: 92%
“…However, although males had more depression that was significantly correlated with disease severity, women were more likely to have greater disease severity. Previous studies have shown similar gender differences in MG severity and QoL with women having worse fatigue and QoL than men [31,32]. Our study is in keeping with those findings.…”
Section: Discussionsupporting
confidence: 92%
“…Although disease severity is often the primary outcome measure in MG clinical trials, fatigue is frequently neglected. As fatigue in MG is multifactorial (in part caused by MG itself, but also affected by muscle deconditioning, steroid use and mental health), further research is needed to understand better how to address this symptom [24]. Interestingly, the current prednisone dose was not associated with either health utility score in contrast with previous studies where the prednisone dose correlated with health-related quality-of-life scores [25].…”
Section: Furthermore Becausementioning
confidence: 68%
“…To the best of our knowledge, the association between RMT [32]. Fatigue in myasthenia affects quality of life and can be reduced after treatment [33]. Our results suggest that adjunctive RMT to conventional drug treatment not only reduce fatigue but also improve outcomes in patients with MG. Due to the characteristic of easily getting fatigued with repetitive exercise in MG, our study protocol did not prefer daily RMT because we consider it inappropriate for MG pathophysiology.…”
Section: Discussionmentioning
confidence: 66%